Digital photography based food intake prediction using artificial neural network - Gunawan, Teddy Surya; Kartiwi, Mira (Malaysian Medical Association, 2017)
Introduction Many wearable devices monitoring have been proposed to complement self-reporting of users’ caloric intake and eating behaviours. These devices comprise varying sensing modalities, such as acoustic, visual, inertial, EEG, EMG, capacitive and piezoelectric sensors. In this research, food intake will be predicted from the input of digital photography using ANN.